Oblique Inguinal Incision in Bernese Periacetabular Osteotomy: Surgical Technique - Lara, Joaquín (J Am Acad Orthop Surg Glob Res Rev, 2017)
OBJECTIVE: To present a modification in the technique of an anterior approach for Bernese periacetabular osteotomy through an oblique inguinal incision. INTRODUCTION: Reorientation of the acetabulum in Bernese periacetabular osteotomy provides adequate coverage of the femoral head, improving biomechanical conditions of the joint without the risk of osteonecrosis. The principal author modified this procedure through an anterior approach with no detachment of the rectus femoris, allowing early rehabilitation. Evolution of scars is an issue both in the original technique and in our modification in terms of hypertrophy, depression, or hyperpigmentation and dehiscence. We introduce an oblique inguinal incision reducing both static and dynamic tension of the skin, allowing healing and avoiding development of unsatisfactory scars. METHODS: Thirty-five surgeries with a modified technique were performed in 27 patients between 2014 and 2016. The average patient age was 27.09 years. No patients were excluded. Development of hypertrophic, depressed, and hyperpigmented scars was evaluated in addition to dehiscence. RESULTS: The average length of the scar was 14.1 cm, and average diastasis was 1.3 mm. There were no hypertrophic, depressed, or hyperpigmented scars. No patients had dehiscence or resutures of surgical wounds. CONCLUSION: Oblique inguinal incision for the anterior approach in Bernese periacetabular osteotomy is a technique that allows healing of surgical wounds without dehiscence or hypertrophic changes by respecting tension lines. It has a high rate of patient satisfaction, with no complications.